2019
DOI: 10.1155/2019/7147128
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Gold Nanorods with Porphyrins for the Potential Treatment of Cancer and Bacterial Diseases: A Critical Review

Abstract: Cancer and bacterial diseases have been the most incidental diseases to date. According to the World Health Report 2018, at least every family is affected by cancer around the world. In 2012, 14.1 million people were affected by cancer, and that figure is bound to increase to 21.6 million in 2030. Medicine therefore sorts out ways of treatment using conventional methods which have been proven to have many side effects. Researchers developed photothermal and photodynamic methods to treat both cancer and bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 289 publications
0
19
0
Order By: Relevance
“…In their study examining the cytotoxicity and genotoxicity of Ag acteristics (Hlapisi, Motaung, Linganiso, Oluwafemi, & Songca, 2019;Zarska et al, 2016). Since they are widely used in biomedicine as contrast agents, drug delivery systems, or as agents in phototherapeutic approaches like PTT (Alkilany, Thompson, Boulos, Sisco, & Murphy, 2012), biosafety of these novel agents must be carefully investigated in great detail.…”
Section: Perez Et Al (2016)mentioning
confidence: 99%
See 1 more Smart Citation
“…In their study examining the cytotoxicity and genotoxicity of Ag acteristics (Hlapisi, Motaung, Linganiso, Oluwafemi, & Songca, 2019;Zarska et al, 2016). Since they are widely used in biomedicine as contrast agents, drug delivery systems, or as agents in phototherapeutic approaches like PTT (Alkilany, Thompson, Boulos, Sisco, & Murphy, 2012), biosafety of these novel agents must be carefully investigated in great detail.…”
Section: Perez Et Al (2016)mentioning
confidence: 99%
“…Au NRs, with their exceptional optical and physical properties, offer a vast array of applications in biomedical technologies, optoelectronic devices, and plasmon‐enhanced spectroscopy. Au NRs are preferred in the diagnosis and treatment of cancer on account of their excellent optical characteristics (Hlapisi, Motaung, Linganiso, Oluwafemi, & Songca, 2019; Zarska et al, 2016). Since they are widely used in biomedicine as contrast agents, drug delivery systems, or as agents in phototherapeutic approaches like PTT (Alkilany, Thompson, Boulos, Sisco, & Murphy, 2012), biosafety of these novel agents must be carefully investigated in great detail.…”
Section: Non‐magnetic Metallic Nanomaterialsmentioning
confidence: 99%
“…All of these characteristics along with the fact that the biological transparency window (~600-1000 nm) coincides with the longitudinal plasmon band of GNRs, ref. [33] make gold nanorods suitable agents to aid in the clinical diagnosis and treatment of cancer with high accuracy and sensitivity, such as through CT-guided photothermal therapy [34,35], photodynamic therapy [36], and cancer radiotherapy [37].…”
Section: Introductionmentioning
confidence: 99%
“…CTAB is used as a soft template in the seed-mediated method. However, studies have shown that it is one major cause of AuNRs toxicity [6][7][8][9]. Therefore, it is essential to find biocompatible, non-toxic, and stable surface modifying agents to passivate Au-NRs and reduce their toxicity whilst maintaining their optical properties [10][11][12].…”
Section: Introductionmentioning
confidence: 99%